Diversification strategy and performance studies: results, measures, and sampling design - Ebrahim Asrarhaghighi; Azmawani Abd Rahman; Murali Sambasivan; Zainal Abidin Mohamed (2013)
Product and international diversified firms play a significant role in the world economy. The number of these firms has increased during time and consequently, assessing the relationship between diversification (product and international) and performance has attracted a lot of attention. However, the results of the studies are inconclusive. This might be due to the differences in measures of diversification and performance, measurement problems, and sampling issues. The aim of this paper is to review the results of the diversification and performance studies and specifically, measurement of diversification, performance and sampling design. Through this review some avenues to improve measurement and sampling in diversification and performance studies are suggested.